Heterophyllin: A New Adenia Toxic Lectin with Peculiar Biological Properties - Massimo Bortolotti; Francesco Biscotti; Andrea Zanello; Letizia Polito; Andrea Bolognesi (Toxins, 2023)
Ribosome-inactivating proteins (RIPs) are plant toxins that were identified for their ability to irreversibly damage ribosomes, thereby causing arrest of protein synthesis and induction of cell death. The RIPs purified from Adenia plants are the most potent ones. Here, we describe a novel toxic lectin from Adenia heterophylla caudex, which has been named heterophyllin. Heterophyllin shows the enzymatic and lectin properties of type 2 RIPs. Interestingly, in immunoreactivity experiments, heterophyllin poorly cross-reacts with sera against all other tested RIPs. The cytotoxic effects and death pathways triggered by heterophyllin were investigated in three human-derived cell lines: NB100, T24, and MCF7, and compared to ricin, the most known and studied type 2 RIP. Heterophyllin was able to completely abolish cell viability at nM concentration. A strong induction of apoptosis, but not necrosis, and the involvement of oxidative stress and necroptosis were observed in all the tested cell lines. Therefore, the enzymatic, immunological, and biological activities of heterophyllin make it an interesting molecule, worthy of further in-depth analysis to verify its possible pharmacological application.